Isu Kontemporer Keuangan Publik Islam - Dzaky Ammar Fauzi; Muhammad Al-Fathi (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
A country must carry out fiscal policy for the welfare of its people. So far, Indonesia has relied on taxes as the largest source of income for the state. If we look more deeply, there are many potentials from Islamic fiscal sources such as waqf and hajj funds. This study uses the library method as a reference. The results of the discussion concluded that waqf and hajj funds have the potential to be a source of state income to be managed.